The Ukrainian question : the Russian Empire and nationalism in the nineteenth century - Miller, A. I. (Alekseĭ Ilʹich), 1959- (Central European University Press, 2003)
This pioneering work treats the Ukrainian question in Russian imperial policy and its importance for the intelligentsia of the empire. Miller sets the Russian Empire in the context of modernizing and occasionally nationalizing great power states and discusses the process of incorporating the Ukraine, better known as "Little Russia" in that time, into the Romanov Empire in the late 18th and 19th centuries. This territorial expansion evolved into a competition of mutually exclusive concepts of Russian and Ukrainian nation-building projects
Keywords: Ukraine -- History -- 1775-1917.; Nationalism -- Russia -- History.; Ukraine -- Relations -- Russia.; Russia -- Relations -- Ukraine.; Russia -- Politics and government -- 1855-1881.; Ukraine -- Histoire -- 1775-1917.; Nationalisme -- Russie -- Histoire.; Russie -- Politique et gouvernement -- 1855-1881.; HISTORY.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism & Patriotism.; Nationalism; Politics and government; International relations; Russia; Ukraine; Nationalismus; Nationalbewegung; Russland; Natievorming.; 1775-1917; Identity, Language policies, Nation-building, Nationalism, Russia, Russian Empire, Ukraine.; Electronic books.; History